Trust me [large type] - Ryan, Hank Phillippi (Thorndike Press large print mystery series., 2019)
"Trust Me is the chilling standalone novel of psychological suspense and manipulation that award-winning author and renowned investigative reporter Hank Phillippi Ryan was born to write. CAN YOU SPOT THE LIAR? An accused killer insists she's innocent of a heinous murder. A grieving journalist surfaces from the wreckage of her shattered life. Their unlikely alliance leads to a dangerous cat and mouse game that will leave you breathless. Who can you trust when you can't trust yourself? "Grief and deception are at the helm of Hank Phillippi Ryan's latest thriller,Trust Me, in which a crime writer and an accused criminal's lives collide, as they come to discover that no one can be trusted, not even oneself. The tension mounts at a blistering pace, while Ryan dazzles on page, weaving a sinister story that readers won't be able to put down."--